Pengaruh Faktor Sosial, Ekonomi, Pemasaran, Terhadap Keberhasilan Budidaya Ikan Nila Metode Keramba Sungai Dusun Sukun - Rohma, Akhmad Sohibur; Nugroho, Matheus (CV. SINAR HOWUHOWU, 2025)
This study examines the influence of social, economic, and marketing factors on the success of tilapia (Oreochromis niloticus) farming using river cage culture in Sukun Hamlet, Pasuruan Regency. A quantitative descriptive approach was applied with total sampling of 35 farmers. Data were collected through questionnaires, observation, and documentation, and analyzed using multiple linear regression. The results revealed that individually social, economic, and marketing factors had no significant effect, but simultaneously they significantly influenced farming success, contributing 59.1%, while 40.9% was explained by other variables outside the model. The findings highlight the importance of integrating social collaboration, economic efficiency, and marketing strategies to enhance aquaculture performance. Recommendations are directed to government and farmer groups to strengthen cooperation, optimize resources, and apply sustainable marketing practices.